Cancer of Unknown Primary Presenting as Bone‐Predominant or Lymph Node‐Only Disease: A Clinicopathologic Portrait. (15th February 2021) - Huey, Ryan W.; Smaglo, Brandon G.; Estrella, Jeannelyn S.; Matamoros, Aurelio; Overman, Michael J.; Varadhachary, Gauri R.; Raghav, Kanwal P.S.
Abstract: Background: Cancer of unknown primary (CUP) presenting as bone‐predominant (BCUP) or lymph node‐only disease (LNCUP) represents two clinically distinct subsets of nonvisceral CUP. These present a diagnostic challenge with a large differential of putative primary cancers and defy the "one‐treatment‐fits‐all" approach. Materials and Methods: We identified patients with BCUP ( n = 29) and LNCUP ( n = 63) using a prospectively collected CUP database and tumor registry of patients seen at MD Anderson Cancer Center between 2001 to 2017. Clinicopathological characteristics, treatments, and outcomes were abstracted. A control group of non‐BCUP/LNCUP cases ( n = 443) from the database was used for comparison. Kaplan‐Meier method was used to estimate overall survival and compared using log‐rank test. Results: In this cohort, 64% and 60% patients had disseminated disease at diagnosis and 39% and 23% had Culine poor‐risk disease in BCUP and LNCUP, respectively. Median overall survival (OS) for BCUP was 14.5 months and for LNCUP was 32.6 months. For BCUP, gemcitabine plus platinum was the most common initial chemotherapy (54%). For LNCUP, carboplatin plus paclitaxel was the most common initial chemotherapy (38%). Radiation was given to 74% of patients with BCUP and 37% of those with LNCUP. On multivariate analysis, poor‐risk Culine group (hazard ratio [HR], 1.76; p < .001) and high neutrophil‐to‐lymphocyte ratio (HR, 2.38, p < .001) were associated with worse OS. Conclusion: BCUP and LNCUP are rare subsets within CUP with varying prognosis. Poor‐risk Culine group and high neutrophil‐to‐lymphocyte ratio are associated with poor survival. Select patients with limited metastases can have long‐term survival with aggressive multimodality treatment. Careful clinicopathological review can facilitate chances of site‐directed therapy. Implications for Practice: Cancer of unknown primary (CUP) rarely presents as bone‐predominant (BCUP) or lymph node‐only (LNCUP) disease. This article describes a cohort of each and compares with a larger CUP cohort. Patients with BCUP have unique issues with fractures and pain, often receiving radiation. Overall survival of 14.5 months was similar to a larger CUP comparison cohort. Patients with LNCUP had improved overall survival at 32.6 months, with longer survival in patients without disseminated disease. Culine poor‐risk group and neutrophil‐to‐lymphocyte ratio were associated with worse overall survival. Tips regarding diagnosis and management of these rare malignant subsets are provided. Abstract : Considering the limited understanding of bone‐predominant or lymph‐node‐only cancers of unknown primary, this article describes the clinical features and outcome data of these two unique conditions.